Quality Improvement of Spent Lubricating Oil - A.-K. Mohamme, Abdul-Halim; M. Kassim, Dhia El-Din; M. Hassan, Huda (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The acidity of spent lubricant was treated using sodium hydroxide solution. The effect of three variables on the treatment have been studied . These are mixing time rangingfrom 5-35 minutes, NaOH to lubricant weight ratio ranging from 0.25-1.25 and weight percentage of NaOH ranging from 2-6 % . The experimental design of Box-Wilson method is adopted to find a useful relationship between the three controllable variables and the lowering in the acidity of the spent lubricant. Then the effective variables and interactions are identified using the statistical analysis(F-test) of three variable fractional design. The mathematical model is well represented by a second order polynomial. By the analysis of the experimental results, the best treatment conditions which achieved an acceptable acidity of the spent lubricant are 20 minutes mixing time , 1 weight ratio of NaOH to spent lubricant and 4.5 weight percentage of N aOH. At these condition the acidity of the lubricant decreases from 0.62 to 0.0602 mg KOH/g oil.